IMF Economic Reviews 98/01 : Press Information Notices. (Economic Issues, 1998)
This chapter provides various IMF staff's concluding remarks of completion of Article IV Consultation with different countries. The IMF holds bilateral consultations under Article IV of its Articles of Agreement with all its member countries, in most cases every year. As part of these consultations, an IMF staff team visits a country to discuss with officials economic developments and the monetary, fiscal, and structural policies that the authorities are following. On its return to IMF headquarters, the team prepares a report analyzing the economic situation and evaluating the stance of policies. That report is then discussed by the Executive Board. At the end of the discussion, the Chairman of the Board summarizes the views expressed by Executive Directors during the meeting. This summing up is transmitted to the country's authorities. In April 1997, Directors agreed to issue, at the request of a member country, the Board's summing up, supplemented by a short account of significant macroeconomic and structural developments at the time of the consultation. In May 1998, the Board decided to have Press Information Notices compiled and published every four months. At the same time, the selection of Article IV consultation summaries was eliminated from the 1998 Annual Report.